The Influence of the Inquiry Model on the Social Studies Content Learning Outcomes of Class IV Students: Study of literature: Pengaruh Model Inquiry Terhadap Hasil Belajar Muatan IPS Siswa Kelas IV: Studi Literatur - Yeti; Wiwik Okta Susilawati; Muhammad Sukron (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This research is motivated by the problem, namely the low social studies learning outcomes of elementary school students. This study aims to determine how the inquiry learning model affects the learning outcomes of social studies content in grade IV elementary school students. The research method used is literature study research. This means reviewing research materials by collecting library data, reading, and recording data from research material sources that have been carried out previously. In this literature study research, the data collection was collected by reference, including 13 journals that were related to the inquiry learning model. From the results of the research that has been obtained, the inquiry model has an effect on the social studies learning outcomes of elementary school students, so that the three main results of the study were found, namely, encouraging student activity, fostering student motivation, and increasing student learning outcomes.